Gazetnaâ metafora i kartina mira - Coneva, Lilâna (Stylistyka, 2006)
The paper analises metaphor in Russian and Bulgarian journalistic discourse. The study is of interest not only because of the similarities between the two languages, but also because of the similarities between the extralinguistic conditions wat generate metafors. The paper discusses major thematic groups of metaphors, specific features of the metaphoric transfer as well as their role in the creation of a picture of the world. The analysis of journalistic metaphors enables is to find the similarities and differences in the metaphoric picture of the world of Russians and Bulgarians.